Scientific approaches to the study of the concept of “regional investment policy” - L. S. Nevyantseva (Вестник университета)
The article considers theoretical aspects in relation to an important category of regional management – regional investment policy. Based on the analysis of the Russian scientific literature, five approaches to understanding the essence of regional investment policy are highlighted and considered by the author: systemic, reproductive, institutional, activity-based, conceptual. Taking into account the studied approaches, the author’s definition of regional investment policy is formulated, based, among other things, on the provisions of the system approach, the theory of interregional economic interaction and the concept of poles of growth. The main objectives of the implementation of the regional investment policy are outlined. In conclusion, the key features of the regional investment policy within the given research vector are summarized and it is concluded that regional investment policy is necessary to expand investment flows between interacting regions and accelerate the economic growth of territories.